Verbal and Communicative Competencies in the Professional Activity of A Teacher - Ismoilov T.I. (Genius Journals, 2023)
This article is devoted to the study of the importance of verbal and communicative competencies in the field of professional activity of a teacher. The authors consider the role of effective verbal communication in the context of the educational environment and emphasize that teachers with a high level of verbal communication skills are able to more effectively influence students, create a productive learning environment and successfully achieve educational goals. The article analyzes the main aspects of verbal and communicative competencies of teachers, including the ability to clearly and effectively express their thoughts, listen and understand the needs of students, adapt their communication style to different age groups and individual characteristics of students. It also discusses methods and techniques that can help educators develop their verbal communication skills, such as training, introspection and feedback.
Keywords: Verbal and communicative competencies; pedagogical activity; educational environment